Pembuatan Layanan Administrasi Desa Melalui Layanan Digital Whatsapp Bagi Warga Desa Harjamekar Kecamatan Cikarang Utara Kabupaten Bekasi - Daspar, Daspar; Hariroh, Fiqih Maria Rabiatul; Rismawati, Rismawati (Abdimas Indonesian Journal, 2023)
This community service activity focuses on creating digital administration services for Simpangan Village, North Cikarang District, Bekasi Regency, which aims to make it easier for residents of Harja Mekar village in North Cikarang District, Bekasi Regency, to obtain administrative services in the village. In community service in Harjamekar Village, North Cikarang District, there are 4 methods used, including observation, interviews, making questionnaires, and counseling.The result has been the creation of a digital administration service using the WhatsApp application as an alternative for the community to obtain information regarding population administration requirements in Harjamekar village, North Cikarang District, Bekasi Regency. Then outreach was carried out to the local community about the benefits and how to use population administration information services via the WhatsApp application and it can be concluded that this service is very helpful and makes it easier for the community to take care of administration in Harjamekar Village, North Cikarang District, Bekasi Regency.